Cooperativa Orellana de Bolívar: propuesta para la producción de orellanas como fuente de ingresos adicionales en el Barrio Vista Hermosa (2020)
Cooperativa Orellana de Bolívar is a social enterprise based on urban agriculture in which a group of families from the Vista Hermosa neighborhood in Ciudad Bolívar will grow orellanas in their homes through the use of a vertical garden and will create a cooperative in order to sell this product to both private clients and restaurants in the city of Bogotá. The purpose of this project is to generate an additional source of income for different families in the town of Ciudad Bolivar (which has the highest poverty rate in the city of Bogotá) and specifically for the families of the Vista Hermosa neighborhood associated with the school Confederación Brisas del Diamante. A business model was developed using industrial engineering tools based on organizational strategy and management such as Porter Analysis, DOFA Matrix, Porter Forces, PESTEL Analysis, etc. In addition, the economic viability of the project was studied through the construction of the Financial Statements of the Cooperative, among which are the Free Cash Flow, the Balance Sheet and the Income Statement. Finally, the Plain Vanilla model was used to calculate the WACC of the project and thus evaluate the relationship between the opportunity cost, the IRR and the NPV.